2016
DOI: 10.1628/001522116x14660601438148
|View full text |Cite
|
Sign up to set email alerts
|

Government Consumption Volatility and the Size of Nations

Abstract: This paper provides empirical evidence showing that smaller countries tend to have more volatile government consumption for a sample of 160 countries from 1960 to 2000. It also shows that country size is negatively related to the discretionary part of government consumption and to the volatilities of most of government consumption items. We argue that the larger size of a country decreases the volatility of government consumption because it acts as an insurance against idiosyncratic shocks, and it leads to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…The literature offers a few studies on the determinants of such volatility. For instance, Furceri and Poplawski-Ribeiro (2009) use data for 160 countries from 1960 to 2000 to prove that country size, proxied by total population, is associated with lower government consumption volatility. This suggests that smaller countries are characterized by more volatile public spending.…”
Section: Government Spending Volatilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The literature offers a few studies on the determinants of such volatility. For instance, Furceri and Poplawski-Ribeiro (2009) use data for 160 countries from 1960 to 2000 to prove that country size, proxied by total population, is associated with lower government consumption volatility. This suggests that smaller countries are characterized by more volatile public spending.…”
Section: Government Spending Volatilitymentioning
confidence: 99%
“…In addition to country size, the literature suggests that both demographic (Albuquerque, 2011;Furceri & Poplawski-Ribeiro, 2009) and macroeconomic (Afonso, Agnello, & Furceri, 2010;Brzozowski and Siwinska-Gorzelak, 2010) factors may potentially affect government consumption volatility, as well as political and institutional ones (Albuquerque, 2011). 3 In general, the level of development is thought crucially to affect public spending volatility, with low-income economies experiencing higher volatility than high-income ones (Furceri et al, 2014).…”
Section: Government Spending Volatilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Ramey and Ramey (1995) presented evidence that government spending volatility has a negative effect on real GDP per capita growth. Looking at the underlying determinants, Furceri and Poplawski-Riberio (2008) found that smaller countries tend to have more volatile government spending, while Agnello and Sousa (2009) observed significant linkages between deficit volatility and the level of economic development, political instability, and inflation, especially in countries with more trade openness. From a macro-fiscal point of view, Fatás and Mihov (2003) showed that numerical fiscal rules tend to lead to a lower degree of volatility in fiscal policy implementation.…”
Section: Theoratical and Empirical Backgroundmentioning
confidence: 99%